Paula von Preradović’ Prosa vor dem Hintergrund der Polemik um die ,christliche Literaturʻ - Michael Sobczak (Colloquia Germanica Stetinensia, 2016)
This article focusses on the prose of the Austrian writer Paula von Preradović (1887–1951) paying special attention to the placement of her works within the context of ‘Christian literature’, a category which is regarded as controversial. Preradović’s literature consists mainly of numerous poems, but she also wrote a novel, short stories, autobiographical sketches, small scenic works and journalistic texts. The Austrian writer composed the lyrics for the national anthem of Austria – Land der Berge, Land am Strome [Land of the mountains, land on the river] (1947).